Brazing - Schwartz, Mel M. (ASM International, 2003)
This second edition of a text on brazing includes revised material on tooling, design, materials, atmospheres, processing, and equipment. Several new topics are covered, including nanostructures and materials, microwave and laser brazing, more effective use of vacuum atmospheres, functionally gradient materials, and intermetallics. There is also more coverage of beryllium alloys, aluminum-lithium alloys, new titanium alloys, ceramic-to-metal brazing, composites, and ceramic-to-ceramic brazing. Case histories and problem-solving examples are included. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com).
Keywords: Brazing.; elektronické knihy; electronic books